Hepatobiliary and Pancreatic Manifestations of Coronavirus Disease 2019 - Singla, Vikas; Arora, Anil (Journal of Digestive Endoscopy, 2020)
Coronavirus disease 2019 (COVID-19) is a new infectious disease that has spread rapidly throughout the world. The disease is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a member of the Coronaviridae family. Though the pulmonary involvement is a major cause of morbidity and mortality, involvement of the gastrointestinal tract, liver, and pancreas has been explained in these patients. The literature is rapidly changing because of influx of new information with every passage of time. The most common hepatic presentation is mild elevation of aspartate transaminase and alanine transaminase, which does not require specific treatment. Occasionally, patients can have severe liver injury. Because of underlying predisposing factors such as diabetes mellitus, hypertension, and obesity, patients with nonalcoholic liver disease may be at risk of severe disease. Patients with decompensated liver disease may also be vulnerable to severe disease. Behavior of SARS-CoV-2 in patients with chronic hepatitis B and C, autoimmune hepatitis, primary sclerosing cholangitis, and primary biliary cirrhosis is yet to be seen. The prevalence and severity of COVID-19 patients with the aforementioned diseases may be different. The effect of SARS-CoV-2 on an underlying liver disease is not known. COVID-19 may complicate the peritransplant period and throw new challenges in these patients. Drugs used to treat severe COVID-19 may cause liver injury and may have an effect on the underlying disease activity. Both hepatic and pancreatic involvement is related to the severity of COVID-19 disease. Serum amylase and lipase levels may be elevated in patients with severe COVID-19 disease. The involvement of pancreatic islet cells may lead to deranged blood sugar levels and potentially predispose to future diabetes mellitus. There are many unknown facts that will unfold with the passage of time.
Keywords: coronavirus disease 2019; hepatobiliary; pancreatic; severe acute respiratory syndrome coronavirus 2